Polydopamine-coated hierarchical tower-shaped carbon for high-performance lithium-sulfur batteries. (1st October 2019) - Jian, Zhixu; Li, Honglei; Cao, Rui; Zhou, Heliang; Xu, Huaizhe; Zhao, Guangjin; Xing, Yalan; Zhang, Shichao
Abstract: Confining the dissolution and diffusion of polysulfide is considered a key factor in the realization of high-performance lithium-sulfur battery. Here, we report a polydopamine (pDA) coated sulfur-carbon composite with a unique hierarchical tower-like structure (S-HTC@pDA) for lithium sulfur cathode. The internal layer by layer structure is capable of uniformly dispersing of sulfur, providing a continuous electronic conductive path and shortening the Li + transport distance, while the external pDA coating can inhibit the diffusion of polysulfide. Benefited from the smart design, the S-HTC@pDA electrode achieved an excellent cycling stability, realizing a high discharge capacity of 916 mAh g −1 at the first cycle and a capacity retention of 79.4% after 500 cycles at 1 C. Therefore, this work provides a new concept in structure design for high performance lithium sulfur cathodes. Graphical abstract: Here, we report a polydopamine (pDA) coated sulfur-carbon composite with a unique hierarchical tower-like structure (S-HTC@pDA) for lithium sulfur cathode. The internal layer by layer structure is capable of uniformly dispersing of sulfur, providing a continuous electronic conductive path and shortening the Li + transport distance, while the external pDA coating can inhibit the diffusion of polysulfide.Image 1 Highlights: Polydopamine coated sulfur-carbon composite with a unique hierarchical tower-like structure has been fabricated. The unique structure of layer-by-layer inner space with pDA coating outside could improve the performance of Li-S cathodes. The S-HTC@pDA electrode exhibits excellent cycling stability.